Under the bridge: autoarchaeoethnographic study of an interstitial space in supermodern Mallorca - Albero Santacreu, Daniel (Complutum, 2021)
Supermodern cities have certain spaces that escape the regulations exerted by the authorities in our living environment. This is the case of interstitial spaces, abandoned areas that are often marginalized by urban planners. This paper presents the results of an autoarchaeoethnographic study focused on the analysis of a 21st Century interstitial space located on the urban periphery of Palma (Mallorca). The methodology used to record the appropriation strategies and practices developed in this space combined direct ethnographic observation with the analysis of materiality. The study aims to address some of the practices developed in such marginal peripheral urban spaces closely related to the non-places characteristic of our current supermodern world. These practices allow us to understand how these spaces work and are conceptualized and to see how they become active elements of our landscape that are crucial for the social development of certain groups and individuals. Through the study of these practices we verified how certain sectors of society make an appropriation and active use of certain marginal public spaces that must be related to large-scale social, economic and historical phenomena. Finally, taking into consideration some of the theoretical foundations of symmetric archeology, we made an assessment of the way in which the very materiality of these spaces (and other elements with which they are associated with) enhance their use as a social space